Prevalence and characteristics of depressive disorders in early adolescents in central Norway - Larsson Bo; Sund Anne; Wichstrøm Lars (BMC, 2011)
Abstract Background Prevalence of depressive disorders among adolescents has varied across studies. The present study aims to assess current and lifetime prevalence and characteristics of adolescent Major Depressive Disorder (MDD), Dysthymia and Depression NOS among adolescents in Central Norway in addition to socio-demographics and use of mental health care. Method In the Youth and Mental Health Study a representative sample of 2432 junior high school students (mean age 14.9 years, SD = 0.6) from two counties in Central Norway were screened with the Mood and Feelings Questionnaire (MFQ). A subset of 345 of these adolescents (72.5% girls), 220 high scorers (MFQ = > 26), 74 middle scorers (MFQ 7-25), and 50 low scorers (MFQ < 7), 1 unknown score, were drawn and interviewed with the Kiddie SADS-PL (Present-Life Version). In all, 79% had parental interviews as well. All estimates of prevalence rates and population shares were weighted back using a sandwich estimator to yield true population estimates. Results Almost one in four subjects (23%) had life-time depression. Prevalences of current Major Depressive Disorder (MDD), Dysthymia and "Double depression" were 2.6%, 1.0% and 0.6%, respectively, and for Depression NOS 6.3%. All depressive disorders were characterized by long duration of episodes with large variations, and for any depressive disorder onset before 12 years of age. In multivariate analyses MDD and Dysthymia were most strongly associated with gender and not living with both biological parents. There was no gender difference for Depression NOS. Although a considerable number of depressed subjects had received mental health care, the reason for contact with services was seldom due to affective symptoms. Less than 20% had been in contact with specialist mental health services. Conclusion High rates of Depression NOS, early onset of depressive episodes, long duration, and low use of specialized services point to the need for improved diagnostic assessment and treatment for young individuals.